Role of TRF2 and TPP1 regulation in idiopathic recurrent pregnancy loss - ERZİK, CAN; ORUN, OYA (ELSEVIER SCIENCE BV, 2019)
Telomeres are the tandem repeats (TTAGGG) present at the ends of the chromosomes that ensure chromosome stability and protect chromosomes from degradation. Telomeres in somatic human cells shorten after every cellular division and are linked to the cellular senescence. In this study we have investigated telomere length and expression of shelterin genes in aborted fetus material from idiopathic recurrent pregnancy losses. Telomere length was measured using Telomere Restriction Fragment Length (TRF) analysis. The gene expression levels for important shelterin complex proteins (TRF1, TRF2, POT1, and TPP1) were determined by Real-time Quantitative Reverse Transcriptase PCR (qRT-PCR). Our results demonstrated down regulation of TRF2 and TPP1 and a strong decline in average telomere length in abort material from women suffering from idiopathic recurrent pregnancy loss. We suggest that shorter telomere length and downregulation of the major shelterin components TRF2 and TPP1 leading to telomere uncapping, might play a critical role in recurrent pregnancy loss. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Idiopathic recurrent pregnancy loss; Universal STELA; Shelterin proteins TRF1; TRF2; TPP1; DOUBLE-STRAND BREAKS; TELOMERE LENGTH; IN-VITRO; MOUSE; FERTILIZATION; SENESCENCE; APOPTOSIS